Violence-related Police Crime Arrests in the United States, 2005-2011 - Brewer, Steven L (2015)
This study is a quantitative content analysis of news reports and court records on 3,328 violence-related arrest cases of 2,586 individual sworn law enforcement officers during the years 2005-2011. The arrested officers were employed by 1,445 nonfederal state, local, special, constable, tribal, and regional law enforcement agencies located in 805 counties and independent cities in 49 states and the District of Columbia. Binary logistic regression and classification and regression tree (CART) analyses were conducted to predict criminal conviction in violence-related police crime arrest cases. Finding indicate that conviction of police officers on one or more offenses charged are driven by specific legal and extralegal factors. Policy implications will be discussed